SPE Asia Pacific Oil and Gas Conference and Exhibition 2010
DOI: 10.2118/132918-ms
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of PDL-Induced Fracture-Face Damage Using a Fracturing Mimicator

Abstract: Simulations with a fit-for-purpose fracture-cleanup model have previously explored the impact of matrix relative-permeability quality on cleanup and productivity in tight-gas sands. Gas-water relative-permeability curves that have a crossover in the range of 0.1% of rel-perm have a region of "rel-perm jail." Previous simulations demonstrated that water invasion in such situations can cause cleanup problems. However, a low rel-perm quality should also act as a fluid-loss-control mechanism during fracturing, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…For instance, the flowback chemical data have been as an alternative approach for a quick characterization of the induced fracture network (Gdanski, 2010, Ghanbari et al 2013, Bearinger 2013. Analysis of salt concentration in the flowback water from hydraulically fractured wells in the HRB indicated that the shape of the salt concentration profiles could be used to evaluate the fracture network complexity (Ghanbari et al (2013 and2015).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the flowback chemical data have been as an alternative approach for a quick characterization of the induced fracture network (Gdanski, 2010, Ghanbari et al 2013, Bearinger 2013. Analysis of salt concentration in the flowback water from hydraulically fractured wells in the HRB indicated that the shape of the salt concentration profiles could be used to evaluate the fracture network complexity (Ghanbari et al (2013 and2015).…”
Section: Introductionmentioning
confidence: 99%
“…At that time, there was no consideration for variable fracture width, only variable conductivity. Pressure-dependent porosity was also discussed as a part of the fracturing mimicator development (Gdanski 2010). Pressure-dependent porosity and permeability were initially intended to be used for simulating the fracturing process.…”
Section: Porosity Loss and Compression Of Gel Phasementioning
confidence: 99%
“…For instance, analysis of flowback chemical data has been as an alternative approach for a quick characterization of the induced fracture network (Gdanski, 2010, Ghanbari et al 2013, Bearinger 2013. Bearinger (2013) qualitatively correlated the complexity of the fracture network and the salt concentration profiles measured during the flowback process.…”
Section: Introductionmentioning
confidence: 99%